Orexin 1 and 2 Receptors in the Prelimbic Cortex Modulate Threat Valuation - Soares, Victor P.M.N. [UNESP]; de Andrade, Telma G.C.S. [UNESP]; Canteras, Newton S.; Coimbra, Norberto C.; Wotjak, Carsten T.; Almada, Rafael C. [UNESP] (Elsevier, 2021)
The ability to distinguish between threatening (repulsors), neutral and appetitive stimuli (attractors) stimuli is essential for survival. The orexinergic neurons of hypothalamus send projections to the limbic structures, such as different subregions of the medial prefrontal cortex (mPFC), suggesting that the orexinergic mechanism in the prelimbic cortex (PL) is involved in the processing of fear and anxiety. We investigated the role of orexin receptors type 1 (OX1R) and type 2 (OX2R) in the PL in such processes upon confrontation with an erratically moving robo-beetle in mice. The selective blockade of OX1R and OX2R in the PL with SB 334867 (3, 30, 300 nM) and TCS OX2 29 (3, 30, 300 nM), respectively, did not affect general exploratory behavior or reactive fear such as avoidance, jumping or freezing, but significantly enhances tolerance and approach behavior at the highest dose of each antagonist tested (300 nM). We interpret these findings as evidence for an altered cognitive appraisal of the potential threatening stimulus. Consequently, the orexin system seems to bias the perception of stimuli towards danger or threat via OX1R and OX2R in the PL.
Keywords: anxiety; beetle mania task; cognitive judgment bias; fear; medial prefrontal cortex; orexin receptors